Yam-harvester that pays for itself - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A root and tuber harvesting machine that reduces crop damage by up to 75% is now available. it was designed by Dr Colin Hudson, of Carib-Agro Industries in Barbados. It is also proving useful for other tropical root crops including tarma, eddo,...